Studying protein folding in health and disease using biophysical approaches. Issue 1 (14th May 2021) - Zhang, Hong; Gong, Weibin; Wu, Si; Perrett, Sarah
Abstract : Protein folding is crucial for normal physiology including development and healthy aging, and failure of this process is related to the pathology of diseases including neurodegeneration and cancer. Early thermodynamic and kinetic studies based on the unfolding and refolding equilibrium of individual proteins in the test tube have provided insight into the fundamental principles of protein folding, although the problem of predicting how any given protein will fold remains unsolved. Protein folding within cells is a more complex issue than folding of purified protein in isolation, due to the complex interactions within the cellular environment, including post-translational modifications of proteins, the presence of macromolecular crowding in cells, and variations in the cellular environment, for example in cancer versus normal cells. Development of biophysical approaches including fluorescence resonance energy transfer (FRET) and nuclear magnetic resonance (NMR) techniques and cellular manipulations including microinjection and insertion of noncanonical amino acids has allowed the study of protein folding in living cells. Furthermore, biophysical techniques such as single-molecule fluorescence spectroscopy and optical tweezers allows studies of simplified systems at the single molecular level. Combining in-cell techniques with the powerful detail that can be achieved from single-molecule studies allows the effects of different cellular components including molecular chaperones to be monitored, providing us with comprehensive understanding of the protein folding process. The application of biophysical techniques to the study of protein folding is arming us with knowledge that is fundamental to the battle against cancer and other diseases related to protein conformation or protein–protein interactions.